A Case Study of Online Learners Participating in the Oregon State University Extension Service Master Gardener Training Program - Bob Rost; Ann Marie VanDerZanden (Journal of Applied Communications, 2002)
As more and more Extension educational content finds its way onto the World Wide Web, questions persist among Extension educators about the effectiveness of online delivery. Do Extension clients learn as much from online Extension educational programs as they do from classroom-based programs? And, are Extension clients with computer and Internet experience more likely to accept online educational programs and be satisfied with them? At Oregon State University, a team of Extension educators addressed those questions via a study of learners participating in the OSU Extension Service’s Master Gardener program. The study compared online learners with traditional classroom learners and included pre- and posttesting, user surveys and correlation analysis.